Analysis Of Basic Economic Sectors In Mojokerto Regency - Winne Ayunda Gaiska; Parikesit Penangsang (Jurnal Multidisiplin Sahombu, 2024)
In development a area, sector Featured will impact on change fundamental in structure economy. Increasing activity base economy causes existence income income. Development of Leading Sectors through determination sector base economy will play a role big in development economy a country. Leading sector can give contribution to formation of regional GRDP as well as have superiority comparative that can give contribution to development economy a area. Study This written use method descriptive quantitative. 200-250 words, 10pt Book Antiqua.